Konfigurasi Muatan Elementer pada Konduktor Persegi dengan Pendekatan Mekanika, Dinamika Listrik, dan Teori Elektromagnetik Matematika - Syamsudin Nur Wahid (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
A conductor, as a material that allows the easy flow of electric charge, plays a crucial role in various electrical and electronic applications. Understanding how elementary charges, particularly electrons, configure and move within a conductor, especially one with a square shape, is essential for analyzing and designing efficient electrical devices. This article discusses the configuration of elementary charges in a square conductor through simulations using a mechanics and electrodynamics approach, focusing on the interactions between charges to achieve a stable configuration. The simulation is conducted by placing charges randomly around the square conductor. The electro-dynamic interactions between charges cause them to arrange themselves in the most stable positions, where each charge interacts to minimize the system's energy. Although a stable configuration is achieved, fluctuations in the total system energy are still observed, approximately 1.33×10⁻³⁵ Joules. These fluctuations indicate that, despite stability, the system continues to experience dynamics that affect the overall energy. Particles at the corners of the conductor move faster than those on other sides, contributing significantly to the measured energy fluctuations. This charge configuration forms an electric field profile in the shape of a square, with the field being concentric, moving from the inside out of the conductor. This indicates that the electric field distribution is more concentrated inside and gradually decreases toward the outside. Furthermore, the distribution of particles on each side of the conductor is not uniform. There are deviations up to 4% from the expected distribution, and these fluctuations occur within a range of ±1 particle. This phenomenon provides deeper insights into the behavior of charges in a square conductor. Understanding this is important for designing electrical and electronic systems. Although the conductor reaches stability, the energy fluctuations that occur still play a role in optimizing electronic devices. The approach combining mechanics and electrodynamics is very useful for understanding the interactions between charges and electric fields, which can be applied to modern electrical technology.